Improving the Properties of Concrete Using Iron Industry Waste - Ali Alajail; Mohamed Ahmed; Abdulmuttaleb Abdullah; Abdullah Ali (African Journal of Advanced Pure and Applied Sciences, 2025)
This study was conducted to investigate the effect of incorporating iron filings on the strength of concrete produced using coarse aggregate from the Majer area in Zliten, fine sand from the Al-Mangoush area in Misrata, and cement supplied by the Arab Union General Contracting Company. comprising cubes with dimensions of 15 × 15 × 15 cm and cylinders measuring 15 cm in diameter and 30 cm in height. The specimens were categorized into three mix design grades (C35, C30, C25). For each grade, 6 control specimens were prepared, along with six specimens for each percentage of iron filings addition (1%, 3%, and 5% by weight of cement). Three specimens from e ach group were tested at 7 days and the remaining three at 28 days, in addition to the reference specimens. The results indicated that adding iron filings as an admixture adversely affects the compressive strength of concrete. However, the study found that a 3% iron filings addition can enhance the splitting tensile strength. Furthermore, incorporating iron filings led to a reduction in concrete density and slump, which strongly suggests that the addition decreases the workability of fresh concrete.